Phenotype profiling of white-nose syndrome pathogen Pseudogymnoascus destructans and closely-related Pseudogymnoascus pannorum reveals metabolic differences underlying fungal lifestyles [version 1; referees: 1 approved, 2 approved with reservations] - Vishnu Chaturvedi (F1000Research, 2018)
Background: Pseudogymnoascus destructans, a psychrophile, causes bat white-nose syndrome (WNS). Pseudogymnoascus pannorum, a closely related fungus, causes human and canine diseases rarely. Both pathogens were reported from the same mines and caves in the United States, but only P. destructans caused WNS. Earlier genome comparisons revealed that P. pannorum contained more deduced proteins with ascribed enzymatic functions than P. destructans. Methods: We performed metabolic profiling with Biolog PM microarray plates to confirm in silico gene predictions. Results: P. pannorum utilized 78 of 190 carbon sources (41%), and 41 of 91 nitrogen sources (43%) tested. P. destructans used 23 carbon compounds (12%) and 23 nitrogen compounds (24%). P. destructans exhibited more robust growth on the phosphorous sources and nutrient supplements (83% and 15%, respectively) compared to P. pannorum (27% and 1%, respectively.). P. pannorum exhibited higher tolerance to osmolytes, pH extremes, and a variety of chemical compounds than P. destructans. Conclusions: An abundance of carbohydrate degradation pathways combined with robust stress tolerance provided clues for the soil distribution of P. pannorum. The limited metabolic profile of P. destructans validated in silico predictions of far fewer proteins and enzymes. P. destructans ability to catabolize diverse phosphorous and nutrient supplements might be critical in the colonization and invasion of bat tissues. The present study of 1,047 different metabolic activities provides a framework for future gene-function investigations of the unique biology of the psychrophilic fungi.